Cytochemical flow analysis of intracellular G6PD and aggregate analysis of mosaic G6PD expression. - Kalnoky, M; Bancone, G; Kahn, M; Chu, C; Chowwiwat, N; Wilaisrisak, P; Pal, S; LaRue, N; Leader, B; Nosten, F; Domingo, G (Wiley, 2017)
Background Medicines that exert oxidative pressure on red blood cells (RBC) can cause severe hemolysis in patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency. Due to X-chromosome inactivation, females heterozygous for G6PD with one allele encoding a G6PD deficient protein and the other a normal protein produce two RBC populations each expressing exclusively one allele. The G6PD mosaic is not captured with routine G6PD tests. Methods An open-source software tool for G6PD cytofluorometric data interpretation is described. The tool interprets data in terms of % bright RBC, or cells with normal G6PD activity in specimens collected from two geographically and ethnically distinct populations, an African-American cohort (US), and a Karen and Burman ethnic cohort (Thailand) comprising 242 specimens including 89 heterozygous females. Results The tool allowed comparison of data across two laboratories and both populations. Hemizygous normal or deficient males and homozygous normal or deficient females cluster at narrow % bright cells with mean values of 96%, or 6% (males) and 97%, or 2% (females) respectively. Heterozygous females, show a distribution of 10-85% bright cells, and a mean of 50%. The distributions are associated to severity of the G6PD mutation. Conclusions Consistent cytoflourometric G6PD analysis facilitates inter-laboratory comparison of cellular G6PD profiles and contributes to understanding primaquine associated hemolytic risk.